Pengaruh Lokasi Usaha, Promosi, Kualitas Layanan Dan Store Atmosphere Terhadap Keputusan Pembelian Pada Brastagi Supermarket Rantauprapat (Studi Kasus Pada Brastagi Supermarket Rantauprapat) - Sianturi, Aprial; Nasution, Ade Parlaungan; Sumitro, Sumitro (LPPM Universitas Labuhanbatu, 2020)
At this time, consumers not only make a purchase decision just because it is in accordance with their wants and needs or because the price is affordable or cheap but consumers will also decide on the purchase of a product or item by looking at the location, business promotion used, quality of Service and atmosphere or armosphere in the store. Purchasing decisions made by consumers will be influenced by the goods offered price, product, atmosphere, service, location of the company or store. Purchasing decisions are made by consumers with considerations that really support and can benefit the buyer. The population in this study is the customer in Brastagi Supermarket Rantauprapat with a sample determined using the formula that is rounded Wibisono to 100 people. Data collection using research questionnaires distributed directly by researchers in order to obtain primary research data. Analsisis technique used in processing the data used multiple regression test to answer the research hypothesis. The results showed that partially the business location has a positive and significant effect on purchasing decisions in Brastagi supermarket Rantauprapat with a value of T1 count of 2.362 > ttable of 1.660 with a significance of 0.020 < 0.05. Promotion has a positive and significant effect on purchasing decisions in Brastagi supermarket Rantauprapat with T2 count value of 2.101 > ttable of 1.660 with significance of 0.038 < 0.05. Quality of Service has a positive and significant effect on purchasing decisions in Brastagi supermarket Rantauprapat with a value of T3 count of 2.012 > ttable of 1.660 with a significance of 0.047 < 0.05. Store Atmosphere has a positive and significant effect on purchasing decisions with a value of T4 count of 2.836 > ttable of 1.660 with a significance of 0.006 < 0.05. Simultaneously business location, promotion, quality of Service and store atmosphere positive and significant to the purchase decision in Brastagi supermarket Rantauprapat with Fhitung value of 54.042 > from Ftable 3.09 with significance level 0.000 < 0.05 at the level of confidence 95% and Alpha 5%.